1998
DOI: 10.1210/endo.139.12.6340
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) 38 and PACAP27 Activate Common and Distinct Intracellular Signaling Pathways to Stimulate Growth Hormone Secretion from Porcine Somatotropes1

Abstract: We have recently shown that the two bioactive forms of pituitary adenylate cyclase-activating polypeptide, PACAP38 and PACAP27, stimulate GH release and GH messenger RNA (mRNA) accumulation in cultured porcine pituitary cells. However, dose- and time-related differences in the response to both peptides suggested that the signaling mechanisms activated by PACAP38 and PACAP27 in this cell type could differ. To test this hypothesis, we have evaluated hormone release and GH mRNA content after PACAP treatment in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This PACAP-mediated increase in intracellular Ca 2ϩ concentration occurs by influx of Ca 2ϩ through voltage-dependent Ca 2ϩ channels, including L-type Ca 2ϩ channels and/or by release of Ca 2ϩ from intracellular stores via a phospholipase C-␤ (PLC)-mediated pathway (42,49,(52)(53)(54). The data presented here delineate steps in the pathway involved in modulation of L-type Ca 2ϩ channels by PACAP and subsequent increase in Ca 2ϩ influx through these channels.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This PACAP-mediated increase in intracellular Ca 2ϩ concentration occurs by influx of Ca 2ϩ through voltage-dependent Ca 2ϩ channels, including L-type Ca 2ϩ channels and/or by release of Ca 2ϩ from intracellular stores via a phospholipase C-␤ (PLC)-mediated pathway (42,49,(52)(53)(54). The data presented here delineate steps in the pathway involved in modulation of L-type Ca 2ϩ channels by PACAP and subsequent increase in Ca 2ϩ influx through these channels.…”
Section: Discussionmentioning
confidence: 80%
“…PACAP mediates a number of physiological functions (19,38), such as somatodendritic vasopressin release (39), catecholamine secretion (40,41), growth hormone secretion (42), secretin release (43), gene expression (44,45), neuronal protection from apoptosis (46), effects on muscle excitability (47, 48), circadian rhythms (44,49), and behavioral and psychomotor phenomena (50,51). Many of these processes are mediated via Components examined in the present study, as well as those studied in two previous reports from this laboratory (16,26), are shown boxed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been shown that several other hypothalamic hypophysiotropic neuropeptides are involved in GH regulation in vertebrates [ 21 ], including the pituitary adenylate cyclase-activating polypeptide (PACAP) [ 32 ], thyrotropin releasing hormone (TRH) [ 33 ]; and gonadotropin releasing hormone (GnRH) [ 34 ]. Thus, PACAP has been described as a stimulator of GH secretion in fish [ 35 ], amphibians [ 36 ], and birds [ 37 ], while in mammals it has shown differential responses, being stimulatory in rats [ 38 ] and pigs [ 39 ] but without effect or even inhibitory in sheep [ 40 ]. Likewise, TRH modulates the release of GH in fish [ 41 ], amphibia [ 42 ], reptiles [ 27 ], birds [ 43 ], and mammals [ 44 ].…”
Section: Introductionmentioning
confidence: 99%